PSYCHOSOCIAL WORK WITH PARENTS OF PEOPLE WITH DISABILITIES - Радченко, Марина Ігорівна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The problem of social and psychological rehabilitation of parents having children with special needs. Highlights the various forms of assistance to such families. Proposed training course of personal growth that takes into account the specifics of personal self parents of children with disabilities. Described the results of formative experiment. We present average that demonstrate the effectiveness of each training session. Emphasized the complex nature and regular social and psychological rehabilitation of families of children with disabilities